Counseling of The Danger of Rhodamin-B in Chili Sauce Around of The Traditional Market Tanjung Morawa - Sinurat, Jhon Patar; Br Karo, Reh Malem; Sirait, Reni Aprinawaty; Yanti, Dian Anggri (JURNAL PENGMAS KESTRA (JPK), 2023)
Food products currently compete with each other based on price and physical appearance. Many traders are competing to make food with attractive colors by adding synthetic dyes. However, in order to make big profits, there are some who make food products but are not honest. Such as adding rhodamine-B, which is a textile dye, as a coloring agent in foods such as chili sauce. People often use chili sauce to add a spicy taste to food. If there is rhodamine-B in food, it can cause health problems such as stomach inflammation, skin irritation, respiratory tract and liver cancer and can cause death if it accumulates in large quantities. This community service activity through outreach will increase public knowledge about the dangers of rhodamine-B. Where PkM material will be presented through lecture, discussion and question and answer methods. The number of PkM participants is 20 traders who sell around the Tanjung Morawa traditional market, where PkM participants are determined randomly. The increase in participants' knowledge was measured through pre and post-tests. The service results show that there are several chili sauce products that contain certain levels of rhodamine-B so it is not recommended to use this chili sauce. Apart from that, through this outreach activity, PkM participants experienced an increase in average knowledge about the dangers of rhodamine-B by 26.5. Where the average pre-test score is 52 and post-test is 78.5, which means there is an increase in knowledge after the counseling activities.